Entrepreneurship Orientation to Nurture the Halal Food Industry Future in Ethiopia - Gemechis Fikadu; Kenesa Kebede; Shashi Kant (Journal of Islamic Economic and Business Research, 2023)
The concept of entrepreneurship is not unique in Islam, as observed from history, that the Prophet and His disciples engaged in it as a respectable profession. Islamic economic academics recently invented the term "Halal entrepreneurship" or "Halalpreneurship" to describe and separate business owners in the Halal market from those in other industries. Islamic ideas are incorporated into business owners in the Halal sector, reshaping them through certain traits that permit the usage of the phrases "Halalpreneurs" and "Halalpreneurship." But defining Halalpreneurship has only been addressed in a few number of scholarly papers. In this sense, this chapter aims to achieve two main objectives. To properly introduce Halal entrepreneurship (Halalpreneurship), it is first necessary to highlight the salient features that distinguish it from other forms of business. Researchers assessed RMSEA levels under 0.05 to be good, between 0.05 and 0.08 to be acceptable, between 0.08 and 0.1 to be marginal, and over 0.1 to be poor, all in accordance with some theoretical underpinnings. Here, all latent item covariance was greater than 0.70, indicating a good match.Â  One will be able to recognize their position as a Halalpreneur in the Halal industry with the help of such understanding and knowledge. The impact of exposure on the outcome is the direct effect in the absence of the mediator. The effect of exposure on the outcome of mediation is the working indirect pathway.